Regional Expenditure Allocation Optimal Point Simulation Using Data Development Programming in Achieving a Resilient Regional Economy in East Java - Britany Sembiring Sembiring (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2020)
This study aims to find the optimal point of the allocation of local government spending to increase economic growth in the region and create a resilient economy. The methods used are (1) clustering regional potential based on LQ and the level of pandemic impact based on the Covid Intensity Index; (2) efficiency measurement and benchmarking of local government expenditure allocation using DEA; (3) development of an alloxy optimal point simulation application using LP, and; (4) robustness testing using the OLS method. This study uses input data originating from realization based on the functions of 509 local governments in 2019 and 2020, HDI, PMTB, Manpower, and output in the form of GRDP growth. The results of this study show that the efficiency of local government expenditure allocation management has a positive correlation with economic growth. The results of this analysis are specific recommendations for each region in achieving the most optimal level of growth and efficiency. This simulation can provide a solution on how to manage APBD management as a government intervention to increase the economic resilience of the economy against the impact of the pandemic as well as under normal circumstances.